EXONERATION CLAUSE ON LAW OF CONSUMER PROTECTION: EFFECTS AND LEGAL EFFORTS - Hakim, Jefferson (Jurnal Hukum dan Peradilan, 2019)
Legal disputes between entrepreneurs and consumers are currently caused by several things, one of which is the inclusion of an exoneration clause. The inclusion of the clause has clearly contradicted Law Number 9 of 1999 concerning Consumer Protection and has detrimental to the rights held by the Consumer. In addition, in terms of the Agreement Law, the entreprenurs that includes the exoneration clause clearly does not heed the principle of good intentions by utilizing the weak position of the consumer. The violation of the rights held by consumers, consumers can claim compensation and sue the entrepreneurs through various legal remedies. given by law. In this study also will discuss the legal consequences and legal efforts that can be submitted by the Consumer for the application of the Exoneration Clause in an agreement. The research method that will be used in this research is normative juridical, namely the approach using various data sources such as articles of legislation, various legal theories, and scientific works of scholars. The data used in this study comes from secondary data and tertiary data collected in accordance with the object written. After that, all legal materials that have been collected are inventoried and identified according to the problems that have been formulated. The conclusion of this study is to provide a legal understanding to consumers who are disadvantaged by the inclusion of an exoneration clause and provide advice in the form of legal remedies that can be taken.